2016
DOI: 10.1038/srep23562
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting Stages of Human Kidney Development and Tumorigenesis with Surface Markers Affords Simple Prospective Purification of Nephron Stem Cells

Abstract: When assembling a nephron during development a multipotent stem cell pool becomes restricted as differentiation ensues. A faulty differentiation arrest in this process leads to transformation and initiation of a Wilms’ tumor. Mapping these transitions with respective surface markers affords accessibility to specific cell subpopulations. NCAM1 and CD133 have been previously suggested to mark human renal progenitor populations. Herein, using cell sorting, RNA sequencing, in vitro studies with serum-free media an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 32 publications
1
59
0
Order By: Relevance
“…Table S2 summarizes the FACS data of NCAM, CD133, and EpCAM in fresh and cultured hFK from three different sources.
Figure 2NCAM + CD133 − Cells Grown in mNPEM Contain Early Nephrogenic Lineages that Can Be Dissected according to EpCAM ExpressionMid-gestation hFKs were dissociated and cultured in serum-containing medium (SCM), serum-free medium (SFM), and mNPEM. FACS analysis was performed for NCAM1, a marker that was previously shown to enrich for the CM and early epithelial structures, CD133 (PROM1), a marker that was previously shown to enrich for differentiating and mature epithelial nephron tubules in the fetal kidney, and EpCAM, an epithelial marker (Pode-Shakked et al., 2016, Shapiro et al., 2011). (A) Schematic representation of experiments.(B) Representative FACS analysis of fresh hFK and hFK cultured in either mNPEM, SFM, or SCM for 7 days.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table S2 summarizes the FACS data of NCAM, CD133, and EpCAM in fresh and cultured hFK from three different sources.
Figure 2NCAM + CD133 − Cells Grown in mNPEM Contain Early Nephrogenic Lineages that Can Be Dissected according to EpCAM ExpressionMid-gestation hFKs were dissociated and cultured in serum-containing medium (SCM), serum-free medium (SFM), and mNPEM. FACS analysis was performed for NCAM1, a marker that was previously shown to enrich for the CM and early epithelial structures, CD133 (PROM1), a marker that was previously shown to enrich for differentiating and mature epithelial nephron tubules in the fetal kidney, and EpCAM, an epithelial marker (Pode-Shakked et al., 2016, Shapiro et al., 2011). (A) Schematic representation of experiments.(B) Representative FACS analysis of fresh hFK and hFK cultured in either mNPEM, SFM, or SCM for 7 days.
…”
Section: Resultsmentioning
confidence: 99%
“…Culturing hFK in mNPEM instantly showed morphological heterogeneity, including specific undifferentiated stem cell niches and differentiating epithelial cells, which could be further exploited to show an EpCAM expression gradient (EpCAM − , EpCAM dim , EpCAM bright ) within the NCAM1 + CD133 − hFK cell fraction that was previously suggested to enrich for nephron progenitors (Metsuyanim et al., 2009, Pode-Shakked et al., 2016). This gradient, and especially the NCAM1 + CD133 − EpCAM − hFK cells (a presumed early fraction), were not observed when hFK cells were grown and passaged in SFM or SCM.…”
Section: Discussionmentioning
confidence: 99%
“…Metsuyanim et al and Dekel et al characterized stem cell markers in human fetal kidneys and identified NPC surface markers, namely neural cell adhesion molecule 1 (NCAM1) and frizzled class receptor 7 (FZD7), which enabled the purification of an enriched cell population of human NPCs . Pode‐Shakked et al also demonstrated that purified NCAM1+/CD133– cells cultured in serum‐free media were enriched for SIX2+ NPCs, although those cells quickly differentiated in serum‐free media within a week . A recent study from the same group showed at single‐cell resolution a preservation of uninduced and induced cap mesenchyme as well as a transitioning mesenchymal–epithelial state by dissection of NCAM+/CD133– progenitor cells according to epithelial cell adhesion molecule (EpCAM) expression levels .…”
Section: Generation Of Npcsmentioning
confidence: 99%
“…We next wished to ascertain that AML cells correspond to MSCs in terms of gene expression. Since the kidney harbors several cell lineages (e.g., epithelial progenitors and stromal progenitors) (Pleniceanu et al , ; Dziedzic et al , ), we compared the expression of lineage‐specific renal genes in AML cells to Wilms' tumor [WT, known to arise from epithelial progenitors (Pleniceanu et al , ; Pode‐Shakked et al , ; Shukrun et al , ; Pode‐Shakked et al , )], human fetal kidney (hFK), and human MSCs via qPCR. WT expressed high levels of the entire renal epithelial progenitor gene set, including OSR1 , SIX2 , CITED1 , and PAX2 , compared to hFK (Fig C).…”
Section: Resultsmentioning
confidence: 99%